2015
DOI: 10.1111/apha.12470
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes possess the machinery for 5‐HT synthesis, storage, degradation and release

Abstract: These data reveal coordinated changes in 5-HT production, metabolism and storage that may optimize 5-HT secretion from the CD8(+) T cell subset in response to activation stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…As discussed earlier, four enzymes are involved in the synthesis of melatonin: TPH, AADC, AA‐NAT (also called as NAT), and ASMT (also called as HIOMT). It has been reported that TPH and AADC in T cells also participate in serotonin formation . In addition to TPH and AADC, T cells also express NAT and HIOMT.…”
Section: Melatonin Signaling In T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, four enzymes are involved in the synthesis of melatonin: TPH, AADC, AA‐NAT (also called as NAT), and ASMT (also called as HIOMT). It has been reported that TPH and AADC in T cells also participate in serotonin formation . In addition to TPH and AADC, T cells also express NAT and HIOMT.…”
Section: Melatonin Signaling In T Cellsmentioning
confidence: 99%
“…It has been reported that TPH and AADC in T cells also participate in serotonin formation. 92 In addition to TPH and AADC, T cells also express NAT and HIOMT. Resting PBMCs and PBMCs activated by PHA express NAT and HIOMT and release abundant amounts of melatonin into the culture media.…”
Section: Melatonin Signaling In T Cellsmentioning
confidence: 99%
“…Important genes involved in oxidative stress and detoxification of oxidation by-products are included in this pathway, such as membrane-bound microsomal glutathione S-transferase ( MGST1 ), with a role in the development of inflammation and in cellular defense [101], aldehyde dehydrogenase ( ALDH3B1 ) [102] and monoamine oxidase A ( MAOA ) [103]. Monoamine oxidase A has a role in the metabolism of serotonin: this molecule has been shown to be synthesized, released and degraded also by T lymphocytes [104]). Among the significant genes, we found also some terms significantly overexpressed in other pathways, as AOX1 and CYP2E1 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of serotonin receptors through kinase signaling is a new perspective, with which to continue studying the fluoxetine effect on TauT. T cells can release 5-HT into the extracellular space in response to stimulation [50] . Therefore, it is possible that 5-HT was present in the microenvironment and exerted some effects on its receptors.…”
Section: Discussionmentioning
confidence: 99%